Blood pressure measurement CD-ROM - British Hypertension Society (London : BMJ Books, 1999)
Accompanies recommendations on blood pressure measurement. Special features include instructions on all forms of blood pressure measurement, video sequences and fully searchable text.
System requirements : Multimedia PC level 2 includes : 25 MHz 486SX or compatible microprocessor ; 8MB RAM (16 MB recommended) ; video display resolution of at least 640 x 480 ( 800 x 600 recommended) with 65, 536 (64K) colour; 16 bit sound card , operating system : Windows 3.1, Windows 95 ot Windows NT4.0 ; web browsing software with java script capabilities and MPEG1 playback facilities.
Keywords: Blood pressure determination